Populasi Serangga Hama di Gudang dengan Penciri Atap dan Lantai yang Berbeda di Empat Pasar Lokal Kecamatan Ilir Timur I, Kota Palembang Sumatera Selatan - Ningrahayu, Seviyanti; Herlinda, Siti; Yulistin, Eka; Setyawati, Anita; Anggraini, Erise; Amelia Herwanti, Andriani; Ilmawan, Kalam; Nabila Adinda, Puspa Gemala; Maryati, Maryati; Carsilladepasha, Al Fath (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Ningrahayu, S., Herlinda, S., Yulistin, E., Setyawati, A., Anggraini, E., Herwanti, A. A., Ilmawan, K., Gemala, P. A. N., Maryati, M., Carsilladepasha, F. A. (2024). Population and storage pest spesies from four local markets with various roofs and floors in sub-district of Ilir Timur I, Palembang South Sumatra. In: Ningrahayu et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 823–835). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Food products are agricultural goods imported from overseas and held for extended durations in local warehouses, resulting in pest infestations that cause a yield weight loss of 10.73%. This study aimed to ascertain the prevalence of pest insects in warehouses across several markets in Palembang City. The methodology employed in this observation involved sampling, direct field surveys, and identification utilizing the texts